Forward Modeling of EUV and Gyrosynchrotron Emission from Coronal Plasmas with FoMo - Van Doorsselaere, Tom; Antolin, Patrick; Yuan, Ding; Reznikova, Veronika; Magyar, Norbert (Frontiers in Astronomy and Space Sciences, 2016)
The FoMo code was developed to calculate the EUV emission from optically thin coronal plasmas. The input data for FoMo consists of the coronal density, temperature and velocity on a 3D grid. This is translated to emissivity on the 3D grid, using CHIANTI data. Then, the emissivity is integrated along the line-of-sight to calculate the emergent spectral line that could be observed by a spectrometer. Moreover, the code has been extended to model also the radio emission from plasmas with a population of non-thermal particles. In this case, also optically thick plasmas may be modelled. The radio spectrum is calculated over a large wavelength range, allowing for the comparison with data from a wide range of radio telescopes.